Kontrol Diri dengan Kecanduan Game Online pada Remaja - Wihantama, Aldora; Purnomo, Jusuf Tjahjo (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
The background to this research is that there is a contradiction in the findings of the relationship between self-control and online game addiction in previous research. Apart from that, research is rarely conducted on adolescents because previous findings focused more on adults. This research aims to determine whether there is a negative and significant relationship between self-control and online game addiction in adolescents. This research uses a quantitative descriptive approach. The subjects of this research are adolescent online game players. In this study, a sample size of 101 teenage respondents was used. The data collection technique for this research was carried out by distributing questionnaires. The data analysis technique in this research uses descriptive analysis, classical assumption tests, and interventional analysis using the Pearson Product Moment correlation test. The research results show that there is a significant negative relationship between self-control and online game addiction in adolescents. The result of the determinant coefficient (r2) in this study is (-0.473)2, meaning that self-control has an influence of 22.37%, and means that there are still 77.63% of other variables that impact online game addiction. Implications of this study are expected that adolescents can have good self-control so that when playing online games, they can control themselves so they don't become addicted to playing.